Association of alcohol intake with risk of diabetic retinopathy: a meta-analysis of observational studies - Wei Zhu (Nature Portfolio, 2017)
Abstract Diabetic retinopathy (DR) is a common microvascular complication of diabetes mellitus (DM). The associations of alcohol intake with DR risk have demonstrated contradictory results. Relevant studies were identified by searching electronic databases (Medline, EMBASE and Web of Science) until May 2016. We identified a total of 12,875 DR cases among 37,285 participants in 15 observational studies. The pooled estimation of all the included observational studies was 0.91 (95% CI, 0.79 to 1.06) in a random-effect model. Analyses stratified by study design showed no significant association between alcohol intake and DR incidence in cohort, case control or cross-sectional studies. In the subgroup analyses, neither beer nor spirits intake were associated with DR risk. Furthermore, it was interesting to find that protective effects were detected in the wine (OR = 0.77, 95% CI = 0.64 to 0.92) and sherry (OR = 0.22, 95% CI = 0.05 to 0.95) groups. In conclusion, this current meta-analysis demonstrated that alcohol intake was not associated with risk of DR. Subgroup analysis by alcoholic beverage types showed that wine consumption would reduce the incidence of DR. In the future, more large-scale prospective studies with detailed alcohol subtypes and contents are still warranted to clarify the association.